2017
DOI: 10.1007/s10072-017-3009-3
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of circulating Tfh-Th17 cells in myasthenia gravis patients

Abstract: Recent studies show that the frequencies of circulating follicullar helper T (cTfh) cells are significantly higher in myasthenia gravis (MG) patients compared with healthy controls (HC). And, they are positively correlated with levels of serum anti-acetylcholine receptor antibody (anti-AchR Ab). It is unclear whether cTfh cell subset frequencies are altered and what role they play in MG patients. In order to clarify this, we examined the frequencies of cTfh cell counterparts, their subsets, and circulating pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
3
15
1
Order By: Relevance
“…The importance of IL-21 in MG has been shown to be associated with activated Tfh1 and Tfh17 cells being their major product (23). High frequencies of cTfh-Th17 cells with increased IL-21 mRNA expression confirmed this finding (36). The present study evaluated both Th-and Tfhrelated cytokines.…”
Section: Cytokines In Mgsupporting
confidence: 66%
See 1 more Smart Citation
“…The importance of IL-21 in MG has been shown to be associated with activated Tfh1 and Tfh17 cells being their major product (23). High frequencies of cTfh-Th17 cells with increased IL-21 mRNA expression confirmed this finding (36). The present study evaluated both Th-and Tfhrelated cytokines.…”
Section: Cytokines In Mgsupporting
confidence: 66%
“…ICOS and PD-1 are two molecules closely related to the function of Tfh cells. Previous studies have reported that ICOS and PD-1 are highly expressed on CD4 + CXCR5 + T cells in the PBMCs of AChR-MG patients (22,23,36). As PD-1 was increased on total CD4 + T cells, covering CD4 + CXCR5 + and CD4 + CXCR5 − T cells, we analyzed ICOS expression also in FIGURE 4 | Increase of PD-1 and ICOS expression on the CD4 + T cells of myasthenia gravis (MG) patients.…”
Section: Icos Expression Of Cd4 + T Cell Was Increased In Mgmentioning
confidence: 99%
“…Ocular and generalized MG are the two major clinical forms of the disease. Expansion of cTfh cells, concomitant with expansion of circulating plasmablasts, is observed in patients with MG as compared to healthy control subjects, and is associated with the clinical severity and the form of the disease ( 158 161 ). Strong correlations between cTfh cells and titers of anti-AChR autoantibodies are frequently described ( 159 161 ).…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Expansion of cTfh cells, concomitant with expansion of circulating plasmablasts, is observed in patients with MG as compared to healthy control subjects, and is associated with the clinical severity and the form of the disease ( 158 161 ). Strong correlations between cTfh cells and titers of anti-AChR autoantibodies are frequently described ( 159 161 ). On the contrary, proportions of Tfr cells are decreased in MG patients as compared to controls, leading to an imbalance in the Tfr/Tfh ratio ( 159 , 162 ).…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Circulating follicullar helper T (cTfh) cells are significantly higher in MG and may play a role in the immunopathogenesis and the production of antiAChR Ab [105]. Tacrolimus is a valid option for the management of MG [106].…”
mentioning
confidence: 99%